2018
DOI: 10.4155/fsoa-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for the Platelet-To-Lymphocyte Ratio in Chronic Lymphocytic Leukemia?

Abstract: Aim:The rationale for platelet-to-lymphocyte ratio (PLR) in chronic lymphocytic leukemia (CLL) is that both the platelet and lymphocyte counts are affected by the CLL pathogenesis and could influence treatment decision-making.Methods:Demographic and clinical data of CLL patients diagnosed at our institution between 1989 and 2013 were collected. Cox regression models were used to evaluate the role of PLR in the duration of watchful waiting, postdiagnosis survival and postchemotherapy survival.Results:The data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(22 reference statements)
0
1
2
Order By: Relevance
“…Furthermore, Ahmed et al in a study reported that there was not significant associated between CBC results and advanced Rai stage [26]. Although Bakouny et al did not find significant relation between PLR with the survival of CLL patients [27], there was an inverse correlation between PLR and advanced clinical stages of CLL in our study. Considering the overall findings, we can hypothesis that PLR can act as a prognostic biomarker in CLL patients which requires further investigation.…”
Section: Discussioncontrasting
confidence: 77%
“…Furthermore, Ahmed et al in a study reported that there was not significant associated between CBC results and advanced Rai stage [26]. Although Bakouny et al did not find significant relation between PLR with the survival of CLL patients [27], there was an inverse correlation between PLR and advanced clinical stages of CLL in our study. Considering the overall findings, we can hypothesis that PLR can act as a prognostic biomarker in CLL patients which requires further investigation.…”
Section: Discussioncontrasting
confidence: 77%
“…However, Sall et al study reported that lymphocyte count was signi cantly greater in patients with stage C than groups with stages A or B(24). Furthermore, Ahmed et al in a study reported that there was not signi cant associated between CBC results and advanced Rai stage(25).Although Bakouny et al did not nd signi cant relation between PLR with the survival of CLL patients(26), there was a negative association between PLR and advanced clinical stages of CLL in our study. Taken together, we can hypothesis that PLR can act as a prognostic biomarker in CLL patients which requires further investigation.…”
contrasting
confidence: 70%
“…Regarding hematological diseases, data are rare: No data were available regarding NLR or MLR and different types of newly diagnosed acute leukemia or allogeneic stem cell transplantation. One study reported that PLR did not predict outcome in patients with chronic lymphatic leukemia 22 . In patients with diffuse large B-cell lymphoma, elevated PLR 23 and elevated NLR 24 were associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%